Quote Originally Posted by pickslides View Post
Post PM

From this step:

$\displaystyle a = 5b -2bc - 5c$

We need to isolate $\displaystyle b$ by factoring, recall $\displaystyle ab+ab = a(b+c)$ so

$\displaystyle a = 5\times b -2c\times b - 5c$

$\displaystyle a = b(5 -2c) - 5c$

$\displaystyle a+5c = b(5 -2c) $

Now divide $\displaystyle 5-2c$ from both sides

$\displaystyle b=\frac{a+5c}{5 -2c} $

All good?
Yes I have understood now after some trial and error this afternoon, which might be morning or evening where you are at the other side of the world.

I learned that;

a + 5c = b(5 - 2c) and once I multiplied out the bracket I got; 5b - 2bc. The difficult part for me is seeing b(5 - 2c) before it is factored, just require more practice and some experience, but thank you all who helped.

David